PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK WISATA DI KOTA BATAM - Violetta Cherryline; Linawiati (JURNAL MATA PARIWISATA, 2022)
Consumer Behavior greatly influences customers, in this case tourists in Batam City, to decide to choose and buy tourism products/services? Especially during a pandemic. In addition, factors such as cultural, social, personal and psychological are also very influential in making decisions to buy a tourism product or service. This study elaborates the analysis of PESTLE (Political, Economic, Social, Technological, Environment) and Legal as a tool to monitor whether there are changes that affect customers (tourists) in anticipating the macro situation, namely the covid 19 pandemic to choose and buy tourism products and services. This study uses a quantitative approach, namely the process of finding knowledge using data in the form of numbers as a tool to analyze information about what you want to know to obtain accurate results. This research is limited by the scope of area and substance. For regional scope, it is limited to the research area in Batam City and hinterland islands only. The limitation of research substance only targets research on consumer behavior in Batam, especially workers towards purchasing tourism products or services. Studies on customer behavior or consumer behavior, especially studies on tourists from the domestic market, are very important to study so that stakeholders can make the right strategy in taking a stand. and policies related to tourism